2010
DOI: 10.1016/j.brainres.2010.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Prestin forms oligomer with four mechanically independent subunits

Abstract: Prestin is the motor protein of cochlear outer hair cells (OHCs) with the unique capability of performing direct, rapid and reciprocal electromechanical conversion. Prestin consists of 744 amino acids with a molecular mass of ~81.4 kDa. The predicted membrane topology and molecular mass of a single prestin molecule appear inadequate to account for the size of intramembrane particles (IMPs) expressed in the OHC membrane. Although recent biochemical evidence suggests that prestin forms homo-oligomers, most likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 37 publications
6
46
1
Order By: Relevance
“…3C). Finally, there is a decrease in disparity with shorter ramp durations in the hyperpolarizing direction, and with 140 mM chloride, little disparity exists, which accounts for assertions of good electromechanical coupling during the last couple of decades (8)(9)(10)(11)(12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3C). Finally, there is a decrease in disparity with shorter ramp durations in the hyperpolarizing direction, and with 140 mM chloride, little disparity exists, which accounts for assertions of good electromechanical coupling during the last couple of decades (8)(9)(10)(11)(12).…”
Section: Resultsmentioning
confidence: 99%
“…OHC eM is voltage dependent and necessarily coupled to its charged voltage sensor (8,9,12,26,27,33). Thus, it is expected that sensor-charge movement, measured as displacement currents or NLC, should correspond to mechanical movements of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies of gerbil prestin using Native PAGE and yeast two-hybrid systems suggested a tetrameric state (23), a hypothesis subsequently supported by single particle analysis (5). Recently however, Wang et al (7) used the charge density of prestin in gerbil outer hair cells to conclude that a tetrameric state was possible, but that their data would also be consistent with a dimer. In contradiction to the original hypothesis, Detro-Dassen et al, (6) used copurification, blue native PAGE and chemical crosslinking to show that human SLC26A3, rat, and zebrafish prestin, as well as a SLC26 homologue from Pseudomonas aeruginosa, form dimers with the monomers working in parallel.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although the Glt Ph protein is a trimer and prestin is known to function in homooligomeric form (57, 58), our model does not address the issue of oligomerization. Previous studies have shown that each prestin monomer is mechanically independent in the oligomer (57,58) and interacts with cytoplasmic partners to facilitate the mechanical response.…”
mentioning
confidence: 99%